Motivasi Belanja Hedonis, Gaya Hidup, dan Keterlibatan Fashion pada Pembelian Impulsif - Agustinna, Adhitiya Sheva; Sudarusman, Eka (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2024)
Impulse buying behavior is a phenomenon that occurs in everyday life and is carried out unconsciously by students. This research aims to analyze the influence of hedonic shopping motivation, shopping lifestyle and fashion involvement on impulsive purchases of clothing products for students in Yogyakarta. This research was conducted on students in Yogyakarta. This is because Yogyakarta is a student city with many educational institutions, especially universities, so that it can fulfill research objectives. This research was conducted on students in Yogyakarta for three (3) months, namely from Jun to August 2023. The population in this research was all active students in 2022/2023. The research sample was 125 active students in Yogyakarta in 2022/2023 with purposive sampling as the sampling technique. Data collection techniques were carried out using observation and questionnaires, while data analysis was carried out using multiple linear regression analysis. The research results show that hedonic shopping motivation, shopping lifestyle and fashion involvement have a significant effect on impulsive purchasing of clothing products for students in Yogyakarta.